The systematic position of Hypsugo macrotis (Chiroptera : Vespertilionidae) and a new record from Peninsular Malaysia - Lim, Leesim; Csorba, Gábor; Wong, Chengmin; Zubaid, Akbar; Rahman, Sultana Parvin Habeebur; Kumaran, Jayaraj Vijaya; Khan, F. A A; Huang, Joe Chun Chia; Najimudin, Nazalan; Görföl, Tamás (Magnolia Press, 2016)
The Southeast Asian species of Hypsugo are rare bats, except for H. cadornae and H. pulveratus, which are distributed throughout the Indomalayan region. Hypsugo macrotis is restricted to Peninsular Malaysia, Sumatra, Java and adjacent islands, and is known only from a handful of specimens. Here we report a new locality record of the species from Serem-ban, Peninsular Malaysia, which also represents the first known building-dweller colony of any Hypsugo from the region. We discuss the taxonomic status of two morphologically similar species, H. macrotis and H. vordermanni, and provide the first COI and cyt b gene sequences for H. macrotis and reconstruct the species' phylogenetic relationships.